2006
DOI: 10.1093/eurheartj/ehl272
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for prevention of post-operative atrial fibrillation and its complications after cardiac surgery: a meta-analysis

Abstract: All five interventions reduced the incidence of AF, though the effect of BBs is less than previously thought. The significant reductions in length of stay and stroke in meta-analysis suggest that there are worthwhile benefits from aggressive prevention. Larger studies to confirm these clinical benefits and evaluate their cost-effectiveness would be worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
226
1
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(255 citation statements)
references
References 144 publications
(120 reference statements)
6
226
1
14
Order By: Relevance
“…W większości z tych badań beta-adrenolityki podawano w okresie pooperacyjnym, a za takim schematem ich stosowania przemawia również niedawna metaanaliza [928]. W kilku metaanalizach stwierdzono, że amiodaron zmniejszał częstość występowania AF w okresie pooperacyjnym w porównaniu z beta-adrenolitykiem, a także skracał czas pobytu pacjentów w szpitalu [925,[929][930][931].…”
Section: Prewencja Migotania Przedsionków W Okresie Pooperacyjnymunclassified
“…W większości z tych badań beta-adrenolityki podawano w okresie pooperacyjnym, a za takim schematem ich stosowania przemawia również niedawna metaanaliza [928]. W kilku metaanalizach stwierdzono, że amiodaron zmniejszał częstość występowania AF w okresie pooperacyjnym w porównaniu z beta-adrenolitykiem, a także skracał czas pobytu pacjentów w szpitalu [925,[929][930][931].…”
Section: Prewencja Migotania Przedsionków W Okresie Pooperacyjnymunclassified
“…Dosages vary widely between trials based on body size and LV function. As shown by several RCTs and meta-analyses [183,184,186], amiodarone is effective for the prophylaxis of AF. The largest RCT reported atrial tachyarrhythmias in 16.1% of amiodarone-treated patients compared with 29.5% of placebo-treated patients (HR 0.52, 95% CI 0.34 0.69), a 13.4% absolute risk reduction [184].…”
Section: S28 Esc/eacts Task Force On Myocardial Revascularization / Ementioning
confidence: 98%
“…In a recent metanalysis, Burgess et al 56 demonstrated that patients submitted to biatrial stimulation had 17.7% of POAF, whereas the control group had 35.3% of POAF incidence. Guidelines for the prevention of postoperative AF suggest that biatrial stimulation is a Grade of recommendation A -Level of evidence B 38 .…”
Section: Atrial Stimulationmentioning
confidence: 99%